Cardiovascular risk in obese patients with chronic periodontitis: a clinical controlled study - Juliana Rico Pires; Thaís Uenoyama Dezem; Eliane Marçon Barroso; Benedicto Egbert Corrêa de Toledo; Sally Cristina Moutinho Monteiro; Alex Tadeu Martins; Elizângela Partata Zuza
INTRODUCTION: Studies have shown that obesity is considered a risk factor for the development of periodontal disease and cardiovascular events. OBJECTIVE: The objective was to evaluate the risk for cardiovascular diseases (CVDs) in obese patients with and without periodontal. MATERIAL AND METHOD: One hundred patients were divided into four groups: Group O - obese without chronic periodontitis (n=25); Group OP - obese with chronic periodontitis (n=25); Group NO - non-obese without chronic periodontitis (n=25); and Group NOP - non-obese with chronic periodontitis (n=25). Demographic and laboratorial data (total cholesterol, high-density lipoprotein - HDL and low-density lipoprotein - LDL, triglycerides, and glucose); anthropometric measurements (body mass index - BMI; waist circumference - WC; body fat - BF); blood pressure; and periodontal parameters (bleeding on probing - BOP, periodontal probing depth - PPD, and the clinical attachment level - CAL) were evaluated. Cardiovascular risk was obtained according to the PROCAM's score. The correlation between obesity, periodontal disease and risk for CVD was verified by Spearman's test (α = 0.05). RESULT: The group OP showed a statistically higher rate of PPD > 7 mm (11.2 ± 2.03) when compared with other groups, as well as higher levels of triglycerides, total cholesterol, and LDL (p<0.05). The risk for CVD was statistically higher in the group OP (28.1 ± 3.3) when compared with group O (16.5 ± 3.5), group NOP (12.8 ± 3.9), and group NO (7.7 ± 0.9). Obesity and periodontal disease are directly related to a moderate increase in CVD risk (r = 0.53, p <0.0001 and r = 0.62, p <0.0001, respectively). CONCLUSION: It was concluded that obesity and periodontal disease increases the risk to cardiovascular events.